NCOG-64. INCIDENCE OF EARLY OCULAR COMPLICATIONS AFTER PROTON RADIATION FOR CHILDHOOD BRAIN TUMORS. (9th November 2020) - Bavle, Abhishek; Confer, Michael; Simpson, Hilarie; Gavula, Theresa; Gross, Naina; Lim, Maria; McNall-Knapp, Rene; Collinge, Janine
Abstract: OBJECTIVES: To determine the incidence, timing and risk factors of ocular complications after proton radiation (RT) in childhood brain tumor patients, to better inform screening for these complications. METHODS: We performed a single-institution retrospective review of children treated with proton RT for brain tumors, with ophthalmology data available. Data abstracted included demographics, radiation details and ocular complications (cataract, dry eyes, retinal changes). RESULTS: We treated 81 children with brain tumors, with protons, from 2010-18. Forty three patients with ophthalmology data available, were included in the study, with a median age of 8.3 years (y) (0.8 – 20.6y) (13 craniospinal irradiation/CSI, 27 involved-field radiation/IFRT, 3 whole ventricle). Median follow-up from end of radiation to last eye exam was 2.1y (0.2 – 7.2y). The incidence of ocular complications was 21% (9/43 patients) overall, and 62% (8/13) after CSI. Bilateral cataracts were detected at a median of 3.2y post-radiation, with incidence of 14% (6/43) overall and 38% (5/13) after CSI. Three patients underwent lens replacement. Dry eyes developed in 23% (3/13) of patients during or soon after CSI (0.04 and 0.7y post-RT). One patient with craniopharyngioma developed retinal scarring and cataracts, 2.2y and 3.5y, after IFRT. The median radiation dose to the lenses, for patients with cataract, was 26.02 Gy RBE (4 patients: 19.41 – 31.54). For 3 patients with dry eyes, the median dose (Gy RBE) was 27.93 (11.98 – 28.71) to lenses, 36.96 (25.12 – 47.49) to lacrimal glands and 30.78 (25.08 – 36.49) to corneas (mean doses to bilateral ocular structures). CONCLUSIONS: Children are at risk for cataract and dry eyes after cranial protons, especially CSI, and need ophthalmology follow-up. Larger studies are needed to validate these findings and identify risk-mitigation strategies, with longer follow-up to determine the incidence of ocular complications, and functional outcomes, after cranial proton radiation.